The relationship between fall and loneliness among older people in China: the mediating role of personality trait - Yuan, Luo; Yibo, Wu; Yuqian, Deng; Haiye, Ran; Jiaxin, Liu; Liping, Zhao (Frontiers in Psychiatry, 2023)
Aims: To explore the role of personality trait between fall and loneliness.A questionnaire survey was used to investigate fall, the big five personality traits and loneliness from older people (≥60 years old) in China mainland.Results: A total of 4289 older people participated in the survey. There are significant difference in age, marital status, education level, residence, solitary and fall about loneliness among older people. Especially, falls, only when they occurred one time, would increase the loneliness of older people. Agreeableness, conscientiousness and neuroticism were significant mediating effect between fall and loneliness.Conclusions: This study implied agreeableness, conscientiousness and neuroticism were meditating role between fall and loneliness. In the future, we should consider the big five personality traits more to understand loneliness and offer them interventions for reducing their loneliness. The study design was cross-sectional, so temporal precedence of mediators and causality could not be tested. Because the data were collected retrospectively, current loneliness is likely to have confounding effects on retrospective recall.